Choosing Actuation Scheme for Optimal Performance of 3-DOF Planar Parallel Manipulators. (3rd July 2012) - Babu, S. Ramana; Raju, V. Ramachandra; Ramji, K.
Abstract : This paper describes how the actuation scheme affects the size and shape of the workspace of 3RPR and 3PRR, which are the two popular planar parallel manipulators. This study helps in achieving the required singularity-free zones for a specific task by adopting a suitable actuation scheme without resorting to changing the architecture of the manipulator. In addition, the performance index GCI for each actuation scheme has been evaluated and compared with each other. Finally, the GCI for each actuation scheme has been optimized subjected to the geometric constraints for the 3PRR planar parallel manipulator.